Compressive and flexural strength of concrete containing palm oil biomass clinker with hooked-end steel fibers - Mangi, Sajjad Ali; Mohd Haziman, Wan Ibrahim; Mohd Baharudin, Ridzuan; Burhanudin, M. K.; Norwati, Jamaluddin; Kok, Hui Li; Shahiron, Shahidan; Faisal, Sheikh Khalid; Mohd Fadzil, Arshad; Putra Jaya, Ramadhansyah (Penerbit UTHM, 2018)
This research was carried out to investigate the effects of hooked-end steel fibers on compressive and flexural strength of concrete containing palm oil biomass clinker (POBC) as partial replacement of fine aggregates. The optimum percentage of POBC was taken as 10%, to replace natural sand on the basis of trial mixes. Due to the porous characteristic of POBC, hooked-end steel fibers were added to improve the flexural strength of concrete. For this research, the concrete mixture containing 10% of POBC with varying percentages of the hooked-end steel fibers i.e. 0.2%, 0.4% and 0.6% by weight was produced. Total 48 specimens were prepared, 24 concrete cubes for compressive strength and 24 prisms were prepared for flexural strength at 7 days and 28 days. Hence, it was evaluated that the reduction of workability in concrete with the addition of steel fibers. Furthermore, The maximum flexural strength were recorded as 2.54 MPa with 0.4% hooked-end steel fibers at 28days and maximum compressive strength of was recorded as 27.51 MPa with 0.6% hooked-end steel fibers at 28days. It is concluded that the hooked-end steel fibers has good potentiality to enhance the compressive as well as flexural strength of concrete.